Literature Review : Entomologi Forensik - Faiq Ghosan Alghoniy Albin; Rahmadsyah Rahmadsyah (Inovasi Kesehatan Global, 2026)
Forensic entomology is a branch of forensic science that utilizes insects and other arthropods as biological indicators in death investigations. This discipline plays a crucial role, particularly in cases of advanced decomposition, where conventional forensic methods often face limitations. One of the key contributions of forensic entomology is estimating the post-mortem interval (IPM), or time since death, which can assist investigators in reconstructing the chronology of events. Furthermore, entomological analysis can provide information regarding the location of death, possible movement of the body, and environmental conditions surrounding the crime scene. Common approaches include analyzing insect succession patterns that appear according to the stages of decomposition of the body and determining the age of larvae based on their developmental stage and growth rate. Environmental factors, particularly temperature, humidity, and microhabitat conditions, significantly influence insect development and therefore must be carefully considered in the analysis. This literature review aims to discuss the basic concepts, functions, and role of forensic entomology in law enforcement. Furthermore, this review emphasizes the importance of accurate insect species identification to improve the validity and reliability of the resulting time-of-death estimates.